Improving Efficiency in Robotic Theatres in the Royal Wolverhampton Nhs Trust: A Gynaecology Theatres Perspective. Issue 3 (March 2016) - Harding, V; Williams, J
Improving efficiency within the operating theatre is always a key concern when running a successful operating list. However, with robotic surgery, this can become paramount. Robotic procedures require a more technical set up, additional planning, and good solid communication within the multidisciplinary team. Efficiency needs to be at the forefront of everyone's mind. Forward planning requires knowledge of the procedures being carried out and adequate training with the robot. Trouble shooting will also improve efficiency in robotic surgery, as being able to expect the unexpected can be a major advantage. This article looks at the hurdles encountered by the theatre team at Royal Wolverhampton Trust at the implementation of the robotic programme, and how the theatre team made adjustments to working practice in order to minimise disruption and maximise efficiency.